Exploration of Non-Pharmacological Interventions in Reducing Patient Anxiety in the Operating Room: A Scoping Review - Indra Maulana; Hesti Platini; Salsabila Sakhi Fadila (JURNAL INFO KESEHATAN, 2025)
Preoperative anxiety is a common problem that impacts surgical outcomes and patient well-being. Non-pharmacological interventions offer a safe alternative to managing anxiety without the side effects of medication. This scoping review aims to map the evidence related to non-pharmacological interventions in reducing patient anxiety in the operating room. Following the Arksey and O’Malley framework and the JBI guidelines, a search was conducted in databases such as PubMed and Scopus until August 2025, with inclusion criteria of primary and secondary studies on non-pharmacological interventions in preoperative patients. Data were extracted for variables such as intervention type, population, and effectiveness, and analyzed narratively and thematically. Of the 15 studies, interventions such as music therapy, virtual reality, clown therapy, aromatherapy, and pre-operative education were effective in reducing anxiety by 15-30% in children and adults, with additional benefits on patient satisfaction and physiological stability. Interactive interventions were more effective in children, while sensory therapy was superior in adults. Non-pharmacological interventions are a promising strategy for pre-operative anxiety management, with the need for further research in elderly and emergency surgery populations to strengthen clinical applications.